Thermodynamic analysis of stable and metastable carbides in the Mn-V-C system and predicted phase diagram - Fernández Guillermet, Armando; Huang, Weiming (Comisión Nacional de Energía Atómica; Argentina)
Fil: Fernández Guillermet, Armando. Comisión Nacional de Energía Atómica; Argentina